The effect of industrial waste coal bottom ash as catalyst in catalytic pyrolysis of rice husk for syngas production - Loy, A.C.M. (Elsevier Ltd, 2018)
Comparison between industrial waste coal bottom ash catalyst and commercial catalysts (nickel and natural zeolite) in catalytic pyrolysis of rice husk were investigated in this study. Characterization through X-ray fluorescence (XRF), X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and energy disperse X-ray analysis (EDX), and BrunauerâEmmettâTeller analysis (BET) were carried out to understand the physiochemical activity of the catalysts in pyrolysis of rice husk. The catalyst to rice husk ratio of 0.1 was pyrolyzed in the temperature range of 323â1173 K using thermogravimetric analyzer coupled with mass spectrometer (TGA-MS) equipment to investigate the effect of catalysts in thermal degradation behavior of biomass and syngas production. The study revealed that lowest coke formation (3.65 wt) associated with high syngas (68.3 vol) were attained in catalytic pyrolysis using coal bottom ash catalyst compared to nickel and natural zeolite catalysts. Moreover, the hydrogen concentration had increased 8.4 vol in catalytic pyrolysis of rice husk using coal bottom ash catalyst compared to non-catalytic pyrolysis. Â© 2018 Elsevier Ltd